Rigid motion‐resolved B1+ prediction using deep learning for real‐time parallel‐transmission pulse design. Issue 5 (27th December 2021) - Plumley, Alix; Watkins, Luke; Treder, Matthias; Liebig, Patrick; Murphy, Kevin; Kopanoglu, Emre
Abstract : Purpose: Tailored parallel‐transmit (pTx) pulses produce uniform excitation profiles at 7 T, but are sensitive to head motion. A potential solution is real‐time pulse redesign. A deep learning framework is proposed to estimate pTx B 1 + distributions following within‐slice motion, which can then be used for tailored pTx pulse redesign. Methods: Using simulated data, conditional generative adversarial networks were trained to predict B 1 + distributions in the head following a displacement. Predictions were made for two virtual body models that were not included in training. Predicted maps were compared with ground‐truth (simulated, following motion) B1 maps. Tailored pTx pulses were designed using B1 maps at the original position (simulated, no motion) and evaluated using simulated B1 maps at displaced position (ground‐truth maps) to quantify motion‐related excitation error. A second pulse was designed using predicted maps (also evaluated on ground‐truth maps) to investigate improvement offered by the proposed method. Results: Predicted B 1 + maps corresponded well with ground‐truth maps. Error in predicted maps was lower than motion‐related error in 99% and 67% of magnitude and phase evaluations, respectively. Worst‐case flip‐angle normalized RMS error due to motion (76% of target flip angle) was reduced by 59% when pulses were redesigned using predicted maps. Conclusion: We propose a framework for predicting B 1 + maps online with deep neural networks. Predicted maps can then be used for real‐time tailored pulse redesign, helping to overcome head motion–related error in pTx.